A Miniature Hexa-Band Antenna for Internet of Things Applications Using Six Quarter-wavelength Resonators - Hasan, Y. M.; S. A. Rahman, Z.-A.; Al-Yasir, Y. (Advanced Electromagnetics, 2025)
This work presents a compact, low-cost hexa-band microstrip antenna for Internet of Things (IoT) applications. The proposed hexa-band antenna is composed of simple six-λ/4 resonators to generate six resonant frequencies: GSM 1.84 GHz (1.8 –1.89 GHz), Bluetooth 2.31 GHz (2.25 –2.375 GHz), WiMAX 3.3 GHz (3.16 –3.47 GHz), WiFi 4.63 GHz (4.34 –5 GHz), upper WLAN 6.1 GHz (5.8 –6.91 GHz), and X-band 9.26 GHz (8.87 –9.83 GHz). The proposed hexa-band antenna is fabricated using FR4 substrate with (23 × 20 × 1.6) mm3 dimensions, and its measured results are presented to validate the simulated results. Results from simulations and measurements are used to examine the radiation properties, including radiation patterns, gain, efficiency, VSWR, and reflection coefficient. The proposed hexa-band antenna has a miniaturized size and good radiation performance.